The low serum ferritin as an indicator of inadequate nutrition in international-level female swimmers - Petrov, L.; Kachaunov, M.; Alexandrova, A. (Journal of Applied Sports Sciences, 2024)
Introduction: Iron deficiency is a common feature in athletes, and optimizing iron levels may become a contributing factor to improved athletic performance. Purpose: This study aimed to evaluate body iron stores and their relationship with sports performance. It also sought correlations between the swimmers` hematological, hormonal, anthropometric, and functional status and their sports achievements.